Delirium amongst HIV-infected general medical admissions in Cape Town, South Africa - Day, Cascia (Department of Medicine, 2021)
Background Delirium is associated with increased mortality and hospital length of stay. Limited data are available from HIV-infected acute hospital admissions in developing countries. We conducted a prospective study of delirium amongst acute medical admissions in South Africa - a developing country with universal ART access and high burdens of TB and noncommunicable disease. Methods Three cohorts of adult acute medical admissions to Groote Schuur and Victoria Hospitals, Cape Town, South Africa were evaluated for prevalent delirium within 24 hours of admission. Reference delirium testing was performed by either consultant physicians or neuropsychologists, using the Confusion Assessment Method (CAM). Findings The study included 1182 acute medical admissions; with 318 (26·9%) HIV-infected Median(IQR) age and CD4 count was 35(30-43) years and 132(61-256) cells/mm3 respectively, with 140/318(44%) using ART on admission. Delirium prevalence was 17·6%(95% CI 13·7-22·1%) amongst HIV-infected patients and was an independent risk factor for inpatient mortality. In multivariable logistic regression, factors associated with delirium were age ≥55 years(AOR 6·95[2·03-23·67], p=0·002) and urea ≥15(AOR 4·83[1·7- 13·44], p=0·003), while ART use reduced risk (p=0·014). Low CD4 count, unsuppressed viral load, and active TB were not predictors of delirium; nor were other traditional risk factors such as non-opportunistic, acute infections or polypharmacy. Interpretation Delirium is common and predicts poor outcome in HIV-infected acute medical admissions in endemic settings despite increased ART use. Older HIV-infected patients with renal dysfunction are at high risk for inpatient delirium while those using ART on admission are protected.